Indigenous gut microbiota constitutively drive release of ciliary neurotrophic factor from mucosal enteric glia to maintain the homeostasis of enteric neural circuits - Kato, Ryo; Yamamoto, Takeshi; Ogata, Hanako; Miyata, Kana; Hayashi, Shusaku; Gershon, Michael D.; Kadowaki, Makoto (Frontiers in Immunology, 2024)
It has recently become clear that the gut microbiota influence intestinal motility, intestinal barrier function, and mucosal immune function; therefore, the gut microbiota are deeply involved in the maintenance of intestinal homeostasis. The effects of the gut microbiota on the enteric nervous system (ENS) in the adult intestine, however, remain poorly understood. In the current study, we investigated the effects of the gut microbiota on the ENS. Male C57BL/6 SPF mice at 12 weeks of age were given a cocktail of four antibiotics (ABX) orally to induce dysbiosis (ABX mice). As early as six hours after ABX administration, the weight of the cecum of ABX mice increased to be significantly greater than that of vehicle-treated animals; moreover, ABX-induced dysbiosis reduced the density of enteric nerve fibers (marked by tubulin-β3 immunoreactivity) in the lamina propria of the proximal colon to approximately 60% that of control. TAK242, a TLR4 antagonist, significantly lowered the nerve fiber density in the lamina propria of the proximal colonic mucosa to approximately 60% that of vehicle-treated SPF mice. We thus developed and tested the hypothesis that mucosal glia expressing TLR4 are activated by enteric bacteria and release neurotrophic factors that contribute to the maintenance of enteric neural circuits. Neurotrophic factors in the mucosa of the SPF mouse proximal colon were examined immunohistochemically. Ciliary neurotrophic factor (CNTF) was abundantly expressed in the lamina propria; most of the CNTF immunoreactivity was observed in mucosal glia (marked by S100β immunoreactivity). Administration of CNTF (subcutaneously, 0.3 mg/kg, 3 doses, 2 hours apart) to ABX mice significantly increased mucosal nerve fiber density in the ABX mouse proximal colon to nearly control levels. The effect of CNTF on enteric mucosal nerve fibers was examined in isolated preparations of proximal colon of ABX mice. As it did in vivo, exposure to CNTF in vitro significantly increased enteric mucosal nerve fiber density in the ABX-treated colon. In conclusion, our evidence suggests that gut microbiota constitutively activate TLR4 signaling in enteric mucosal glia, which secrete CNTF in response. The resulting bacterial-driven glial release of CNTF helps to maintain the integrity of enteric mucosal nerve fibers.